Evaluating Internal Control Over Financial Reporting Capacity in Government Ministries and Agencies - Anas Isnaeni; Viska Anggraita (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose: This research aims to evaluate the capacity development of Internal Control over Financial Reporting or Pengendalian Intern atas Pelaporan Keuangan (PIPK), within selected central government ministries and agencies (Kementerian/Lembaga, or K/L). The evaluation is conducted in response to recommendations from the Supreme Audit Agency (Badan Pemeriksa Keuangan, BPK) and findings from the Financial and Development Supervisory Agency (Badan Pengawasan Keuangan dan Pembangunan, BPKP), both of which emphasize the need to enhance the quality and effectiveness of PIPK implementation. Methodology/approach: Employing a qualitative case research design, the research adopts the United Nations Development Programme (UNDP) Capacity Assessment Framework as its analytical lens. The evaluation focuses on four critical dimensions of capacity—namely, institutional arrangements, leadership, knowledge, and accountability—across four selected ministries and agencies. Data were collected through semi-structured interviews, questionnaires, and analysis of relevant documents Findings: The research identifies varying degrees of capacity gaps across the institutions. The most significant gap was found in the leadership dimension, while the accountability dimension exhibited the smallest gap. Key challenges include limited availability of qualified human resources, uneven knowledge management practices, and weak mechanisms for institutional documentation and evaluation. Practical implications: The findings offer valuable insights for policymakers and regulatory bodies to design more targeted capacity-building interventions. These include enhancing leadership engagement, implementing systematic knowledge management strategies, and reinforcing institutional structures to improve the overall effectiveness of PIPK in the public sector. Originality/value: This research represents one of the initial efforts to apply the UNDP Capacity Assessment Framework to the evaluation of PIPK implementation within Indonesian government institutions. It contributes to a deeper understanding of institutional capacity gaps and offers practical recommendations to enhance the reliability and accountability of public sector financial reporting.